2015
DOI: 10.3390/agronomy5020152
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions for Embryo Size and Early Vigour in Multiple Wheat (Triticum aestivum L.) Populations

Abstract: Abstract:Greater early vigour has potential for increasing biomass and grain yields of wheat crops in Mediterranean-type environments. Embryo size is an important determinant of early vigour in barley and likely to contribute to greater vigour in wheat. Little is known of the underlying genetic control for embryo size, or its genetic association with early vigour in wheat. Over 150 doubled-haploid lines in each of three unrelated wheat populations varying for embryo size and early vigour were phenotyped across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The cause of the correlation between embryo size and vigour is unknown, but perhaps larger embryos have more resources readily available for germination and early growth and vigour. The larger embryos in this material are not necessarily a desirable trait if this reduces flour extraction from the total grain, but this effect was found to be relatively small in a mapping population varying for these traits ( Moore, 2004 ).…”
Section: Discussionmentioning
confidence: 97%
“…The cause of the correlation between embryo size and vigour is unknown, but perhaps larger embryos have more resources readily available for germination and early growth and vigour. The larger embryos in this material are not necessarily a desirable trait if this reduces flour extraction from the total grain, but this effect was found to be relatively small in a mapping population varying for these traits ( Moore, 2004 ).…”
Section: Discussionmentioning
confidence: 97%
“…Many efforts have been made to improve these traits by providing good agronomic conditions but the approach has now shifted toward investigating the genetic basis and using it in marker-assisted breeding programs. Studies have also been undertaken to identify quantitative trait loci (QTLs) for seed emergence and early vigor traits in wheat (Maydup et al, 2012 ; Bai et al, 2013 ; Moore and Rebetzke, 2015 ), Arabidopsis (Galpaz and Reymond, 2010 ; DeRose-Wilson and Gaut, 2011 ), tomato (Foolad et al, 2007 ; Khan et al, 2012 ), soy bean (Csanádi et al, 2001 ), barley (Mano and Takeda, 1997 ), and Brassica napus (Hatzig et al, 2015 ). These studies have reported that early vigor traits of seedlings are regulated by a cluster of genes and are strongly affected by environmental conditions (Bettey et al, 2000 ; Koornneef et al, 2002 ; Finch-Savage et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…4) are removed during processing, consumption of immature sweetcorn offers a greater benefit for human Zn nutrition and can be a potential target for further biofortification. It has been suggested that to improve the nutritional value of sweetcorn kernels further, a possible pathway is by breeding for a variety with a larger embryo to endosperm size ratio, as the larger embryo will allow the accumulation of more micronutrients (Nagasawa et al, 2013;Moore and Rebetzke, 2015).…”
Section: Inorganic Nutrient Distribution and Biofortificationmentioning
confidence: 99%